RELIGIOUS SYMBOLS IN WILLIAM BLAKEâ€™S â€œTHE LITTLE GIRL LOSTâ€ AND â€œTHE LITTLE GIRL FOUNDâ€ - Lukas Demon Octovianto Lamanepa; Rr. Arielia Yustisiana (Humaniora Scientia, 2021)
The research aimed to discuss religious symbol in William Blakeâ€™s The Little GirlLost and The Little Girl Found. The objectives of the research were to describewhat the meaning of symbol related to religious symbol. The symbols would berelated to religious symbols as portrayed in the Bible. The theories used in thisstudy were symbolism, religious symbol, Garden of Eden, Innocence, Creation,and Jesus. The technique of data collecting was library research, while themethod of this research was descriptive. There were two approaches used in thisstudy. They were structural and formalist approach. According to the findings ofthis study, religious symbols in The Little Girl Lost and The Little Girl Foundcontained four symbols: the Garden of Eden, Innocence, Creation, and Jesus. TheGarden of Eden explained the situation of Adam and Eve, and the Tree ofKnowledge. Innocence described the main character of this poem, a little girlnamed Lyca. Creation explained the process of creation in this universe, done byGod and the Sabbath. Jesus explained about the Holy Trinity, Lion, Tiger, andCrown of Thorns.Keywords: Religious Symbol, Garden of Eden, Innocence, Creation, Jesus